Tenuous Correlation Between the Snow Depth or Sea Ice Thickness and C- or X-band Backscattering in Nunavik Fjords of the Hudson Strait - Dufour-Beauséjour, Sophie; Bernier, Monique; Simon, Jérome; Homayouni, Saeid; Gilbert, Véronique; Gauthier, Yves; Tuniq, Juupi; Wendleder, Anna; Roth, Achim (2021)
Sea ice is an essential part of the Arctic Ocean and is extremely affected by the global warming. Over the past 30 years, the Arctic has warmed at roughly twice the rate as the entire globe. The Kangiqsujuammiut (people of Kangiqsujuaq, Nunavik, in Canada) observed a later sea ice freeze-up in the fall (Nickels et al., 2011), less snow on the ground, earlier sea ice breakup in spring, changes in travel routes and more variable winds (Cuerrier et al., 2015). These changes influence immensely the Inuits live and have consequences on their personal safety and access to travel and marine wildlife due to ice instability and weather unpredictability (Laidler et al., 2006). Recent work by Yackel et al. showed that, prior to melting onset, the daily variance in C- and Ku-band backscattering is correlated with relative snow thickness (Yackel et al., 2019). The majority of these sea ice applications rely on the C-band (Zakhvatkina et al., 2019). Though, the X-band can adequately discriminate between newly formed ice and its surroundings (Johansson et al., 2018) and is more sensitive to melt onset and surface roughness than the C-band (Eriksson et al., 2010), as well as changes in top-layer snow salinity (Nandan et al., 2017). As for the snow cover, Gill et al. noted that a positive correlation between C-band HH backscattering and snow depth is best observed in cold (-7.9°C) than warm conditions (-0.4°C) (Gill et al., 2015). In contrast, Nandan et al. rather observed that the HH backscattering was greater from a thin snow cover of 4 cm than from snow 8 or 14 cm deep, which they attributed to steeper salinity gradients in thin snow causing enhanced surface scattering (Nandan et al., 2017). They also reported that the HH polarization was more sensitive to snow depth variations than its VV counterpart. This study investigates the correlation between snow depth and sea ice thickness based on field measurements and the SAR backscatter from remote sensing data from 2015 to 2018 focusing the three Nunavik fjords of the Hudson ...